2014
DOI: 10.1007/s10875-014-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Morbidity of Primary Immunodeficiency Diseases, United States 2001–2007

Abstract: Purpose Few studies have estimated population prevalence and morbidity of primary immunodeficiency diseases (PIDD). We used administrative healthcare databases to estimate the prevalence of PIDD diagnoses in the United States from 2001 to 2007. Methods MarketScan databases compile claims from commercial health insurance plans and Medicaid, recording individual diagnoses for outpatient encounters and hospital stays. We used a cross sectional survey to estimate prevalence of PIDD using related ICD-9 codes (279… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 40 publications
2
87
1
4
Order By: Relevance
“…This is supported by data indicating that patients with CVID are diagnosed a mean age of 20–43 years [6, 33, 34] and have several impairments, with chronic lung disease being the most common [4]. Data from the current analysis also indicated that, overall, adult patients with CVID had significantly diminished mental and physical well-being compared with the general US population (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…This is supported by data indicating that patients with CVID are diagnosed a mean age of 20–43 years [6, 33, 34] and have several impairments, with chronic lung disease being the most common [4]. Data from the current analysis also indicated that, overall, adult patients with CVID had significantly diminished mental and physical well-being compared with the general US population (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Although primary immune deficiency disorders (PIDDs) are considered ‘rare diseases’, both the incidence and the prevalence of those disorders are increasing . With this increase, it is reasonable to anticipate that the demand for immunoglobulin replacement therapy (IgGRT) would increase.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, there were an estimated 6 million people living with PID worldwide [3], with PID affecting 29.1–50.5 per 100,000 [4]. It is likely that prevalence of PID will continue to increase as the extended recognition of these diagnoses grows, significantly affecting both adults and children at the population level [3].…”
Section: Introductionmentioning
confidence: 99%